Cross Cultural Learning at a Crossroad: Making a Difference in Intercultural Adult Education in Sub-Saharan Africa - Tangyie Evani; Beatrice Kom; Edmond Biloa; Sonny Roland Blinga (Adult Education Research Conference, 2014)
Approaches in achieving and implementing a shared vision for adult education concept applicable to SubSaharan African contexts are almost nonexistent when it concerns strategies conceived within the global context. This situation has limited the understanding of complex efforts on building sustainable development oriented educational mechanisms that will lead to more effective and adequate contextual results in African states south of the Sahara.